Analisis Psikoanalitik Tokoh Qais dalam Syair "Layla Majnun" Karya Nizami Ganjavi - Priscilla Audzah; Doni Wahidul Akbar (Shaut al Arabiyyah, 2024)
The classic story of the poem "Layla Majnun" which presents a tragic love story and becomes one of the famous love stories in the Persian literary tradition. The problem raised from this research is How to Analyze Sigmud Freud's theory in the sy'ir "Layla Majnun", and How to Psychoanalytic Qais in the poem "Layla Majnun" using Freud's psychoanalytic theory framework. The purpose of this research is to analyze the psychology experienced by Qais figures using a psychoanalytic approach, which underlies the relationship between psychology and love. As well as producing about how psychology in Qais love can be applied in today's life. It can be associated with love problems that often occur in teenagers today. The method used in this study is descriptive qualitative, where the verse text is analyzed in depth to identify the psychological elements that underlie the Qais character. Research results show that id Qais encourages a strong desire to love Layla, while the ego tries to balance that desire with the existing reality. The superego plays a role in creating guilt and moral conflict, which in turn worsens Qais's emotional state. In addition, ego defense mechanisms such as Repression, Sublimation, Projection, Displacement, Rationalization, Reaction Formation, and Regression help explain how Qais deals with emotional pain and internal conflicts he experiences. This research is expected to contribute to the understanding of the relationship between psychology and literature, as well as open up space for further research in the field of literary analysis and psychology.